A novel NOX2 inhibitor attenuates human neutrophil oxidative stress and ameliorates inflammatory arthritis in mice - Liu, Fu-Chao (Redox Biol, 2019)
Neutrophil infiltration plays a significant pathological role in inflammatory diseases. NADPH oxidase type 2 (NOX2) is a respiratory burst oxidase that generates large amounts of superoxide anion (O(2)(•−)) and subsequent other reactive oxygen species (ROS). NOX2 is an emerging therapeutic target for treating neutrophilic inflammatory diseases. Herein, we show that 4-[(4-(dimethylamino)butoxy)imino]-1-methyl-1H-benzo[f]indol-9(4H)-one (CYR5099) acts as a NOX2 inhibitor and exerts a protective effect against complete Freund's adjuvant (CFA)-induced inflammatory arthritis in mice. CYR5099 restricted the production of O(2)(•−) and ROS, but not the elastase release, in human neutrophils activated with various stimulators. The upstream signaling pathways of NOX2 were not inhibited by CYR5099. Significantly, CYR5099 inhibited NOX2 activity in activated human neutrophils and in reconstituted subcellular assays. In addition, CYR5099 reduced ROS production, neutrophil infiltration, and edema in CFA-induced arthritis in mice. Our findings suggest that CYR5099 is a NOX2 inhibitor and has therapeutic potential for treating neutrophil-dominant oxidative inflammatory disorders.